Musical hearing and the acquisition of foreign-language intonation - Jekiel, Mateusz; Malarski, Kamil (Studies in Second Language Learning and Teaching, 2023)
The present study seeks to determine whether superior musical hearing is correlated with successful production of second language (L2) intonation patterns. Fifty Polish speakers of English at the university level were recorded before and after an extensive two-semester accent training course in English. Participants were asked to read aloud a series of short dialogues containing different intonation patterns, complete two musical hearing tests measuring tone deafness and melody discrimination, and a survey regarding musical experience. We visually analyzed and assessed participants’ intonation by comparing their F0 contours with the model provided by their accent training teachers following ToBI (Tones and Break Indices) guidelines and compared the results with the musical hearing test scores and the survey responses. The results suggest that more accurate pitch perception can be related to more correct production of L2 intonation patterns as participants with superior musical ear produced more native-like speech contours after training, similar to those of their teachers. After dividing participants into four categories based on their musical hearing test scores and musical experience, we also observed that some students with better musical hearing test scores were able to produce more correct L2 intonation patterns. However, students with poor musical hearing test scores and no musical background also improved, suggesting that the acquisition of L2 intonation in a formal classroom setting can be successful regardless of one’s musical hearing skills.